Effectiveness of The Daya Flat Development in Empowering the Poor Community in Biringkanaya District, Makassar City - Udas, Udas; Supiana, Ilham; Suwirya, Suwirya (CV. Green Publisher Indonesia, 2025)
The development of adequate housing is one of the main challenges in improving community welfare, especially for low-income groups in urban areas. This research aims to evaluate the effectiveness of Rusunawa Daya development in empowering the poor in Biringkanaya Sub-district, Makassar City. The method used is descriptive qualitative with data collection through observation and interviews with residents and the Housing and Area Settlement Agency (DPKP). The results showed that the construction of Rusunawa Daya succeeded in meeting the needs of decent housing for low-income people and improving the quality of life of residents. As many as 97% of residents reported improvements in their economic and social conditions after living in the Rusunawa. However, challenges remain in adjusting to the new environment and behaviors carried over from the previous residence. DPKP is expected to pay more attention to environmental management and community empowerment so that the potential of Rusunawa can be maximized. This research provides recommendations to increase residents' participation in Rusunawa management and create sustainable programs to improve quality of life.